2016
DOI: 10.3892/ol.2016.4152
|View full text |Cite
|
Sign up to set email alerts
|

Continuous negative pressure-flush through a dual tube for the treatment of a complicated pharyngeal fistula: A case report

Abstract: The treatment of pharyngeal fistulas is complicated. It is more difficult to deal with pharyngeal fistula following surgical treatment for hypopharynx carcinoma, particularly in cases of pectoralis major muscle flap repair. The present study describes the case of a 56-year-old man who presented with a highly-differentiated pharyngeal squamous cell carcinoma located at the right side of the hypopharynx. The patient underwent a total laryngectomy and a right functional carotid dissection and tracheostomy; this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…At present, owing to variations in surface topography and the existence of five sense organs, use of NPWT for PCF has not been studied extensively despite having been used in complicated wound healing for decades. Teixeira et al investigated NPWT as a topical negative pressure dressing and Zhang et al evaluated the availability of continuous negative pressure flush through a dual tube 44,45 . However, most of the relevant research has focused on the external fistula orifice, with only a limited number of studies having investigated treatment of the internal fistula orifice 42,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, owing to variations in surface topography and the existence of five sense organs, use of NPWT for PCF has not been studied extensively despite having been used in complicated wound healing for decades. Teixeira et al investigated NPWT as a topical negative pressure dressing and Zhang et al evaluated the availability of continuous negative pressure flush through a dual tube 44,45 . However, most of the relevant research has focused on the external fistula orifice, with only a limited number of studies having investigated treatment of the internal fistula orifice 42,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Teixeira et al investigated NPWT as a topical negative pressure dressing and Zhang et al evaluated the availability of continuous negative pressure flush through a dual tube. 44,45 However, most of the relevant research has focused on the external fistula orifice, with only a limited number of studies having investigated treatment of the internal fistula orifice. 42,46 Loeck et al found that endoscopic vacuum therapy could promote closure of a PCF by treating the internal fistula orifice.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NPWT is reported in 3 articles; Teixeira et al 10 described it as a topical negative pressure dressing, in 1 case Loeck et al 11 showed the results obtained with the endoscopic negative-pressure therapy (ENPT), and in another study Zhang et al 12 illustrated the effectiveness of a continuous negative pressure-flush through a dual tube. The length of the treatment ranges between 14 and 60 days (mean 31.8 days).…”
Section: Negative-pressure Wound Therapy (Npwt)mentioning
confidence: 99%
“…It is interesting to note that both patients were discharged home 6 days after initiating NPWT, given the favourable clinical evolution, and could continue treatment in an outpatient basis, thus reducing the length of hospital stay. Loeck 11 and Zhang 12 proposed modifications of the classical NPWT; the former used endoscopic negative-pressure therapy (ENPT) in 1 patient while the latter treated 1 patient with continuous negative pressure-flush through a dual tube. The ENPT consisted of placement of a drain device at the wound site, and application of a controlled continuous negative pressure after connecting drainage tube to an electronic vacuum pump.…”
Section: Negative-pressure Wound Therapy (Npwt)mentioning
confidence: 99%